The validation of a portable force plate for measuring force-time data during jumping and landing tasks - Walsh, M. S.; Ford, K. R.; Bangen, K. J.; Myer, G. D.; Hewett, T. E. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to determine the reliability and validity of a portable force plate when analyzing jumping and landing tasks. Subjects performed 3 drop vertical jumps and 3 drop landings on both a standard strain gauge laboratory force plate and a portable force plate. In contrast to typical laboratory installed force plates, the portable 6-component force plate can be easily transported and used onsite at various training or data collection sites and incorporates Hall effect technology. The measured parameters included maximum force and time to maximum force for initial stance of the both tests, maximum takeoff force, and time to maximum takeoff force for the drop vertical jump. The Pearson correlation coefficients for the drop landing and the drop vertical jump for maximum force (r = 0.942, r = 0.940), time to maximum force (r = 0.891, r = 0.920) and for drop jump maximum jumping force (r = 0.971), and time to maximum takeoff force (r = 0.917) were all high and indicate that the force data collected by a resistor-type portable force plate provide similar measures to a standard strain-gauge laboratory force plate. Additionally, the within session reliability of the drop landing and the drop vertical jump measured by the portable force plate showed high interclass correlation coefficients for examined variables of 0.979 and 9.67 for maximum landing force and 0.917 and 0.920 for time to maximum landing force, respectively. The interclass correlation coefficients for the maximum takeoff force and time to maximum takeoff force during the drop vertical jump were 0.991 and 0.86. The results indicate the force and timing measurements from the portable force plate were both valid and reliable. Use of the portable force plate may facilitate methods of force measurement that can be applied out into the field and therefore a valuable tool for on site landing and jump force measurements in a variety of settings for large numbers of subjects.